In vitro evaluation of electrospun silk fibroin/nano-hydroxyapatite/BMP-2 scaffolds for bone regeneration. Issue 3 (11th February 2017) - Niu, Bingjie; Li, Bin; Gu, Yong; Shen, Xiaofeng; Liu, Yong; Chen, Liang
Abstract: Bone tissue engineering by using osteoinductive scaffolds seeded with stem cells to promote bone extracellular matrix (ECM) production and remodeling has evolved into a promising approach for bone repair and regeneration. In order to mimic the ECM of bone tissue structurally and compositionally, nanofibrous silk fibroin (SF) scaffolds containing hydroxyapatite (HAP) nanoparticles and bone morphogenetic protein 2 (BMP-2) were fabricated in this study using electrospinning technique. The microstructure, mechanical property, biocompatibility, and osteogenic characteristics were examined. It was found that the HAP nanoparticles were successfully incorporated in the SF nanofibers (diameter, 200–500 nm). The mechanical properties of SF/HAP/BMP-2 composite scaffolds increased with HAP content when it was less than 20 wt%, after which the mechanical properties dropped as HAP content increased. Cell culture tests using bone marrow mesenchymal stem cells (BMSCs) showed that the scaffolds had good biocompatibility and promoted the osteogenic differentiation of BMSCs. Therefore, the electrospun SF/HAP/BMP-2 scaffolds may serve as a promising biomaterial for bone tissue engineering. Graphical Abstract: Electrospun nanofibrous silk fibroin/hydroxyapatite/bone morphogenetic protein 2 composite scaffolds showed improved mechanical properties and promoted osteogenic differentiation of bone marrow mesenchymal stem cells.